(untitled) (Modern education and development, 2024)
In the evolving landscape of modern education, teacher professional development (TPD) has become essential to ensuring high-quality teaching and enhancing student achievement. This article examines the role of professional development in equipping teachers with the skills and knowledge needed to address today’s educational challenges. Through a mixed-methods study involving surveys and classroom observations, this research identifies the impact of TPD on teaching effectiveness and highlights best practices for implementing impactful TPD programs. Findings suggest that structured, collaborative, and context-driven TPD significantly improves teaching practices, thereby promoting better student engagement and academic outcomes.